2020
DOI: 10.5937/ekoizazov2017105d
|View full text |Cite
|
Sign up to set email alerts
|

Commercials and its impact on consumers: Children abuse in advertising

Abstract: The modern era of capitalism is characterized by mass production. Consumer society is the target of producers whose demand depends on financial success of companies. An important correlation between consumers and producers is created by advertising and propaganda activities. Traditional and new media through which the advertising message is conveyed play an important mediating role. Marketing agencies nowadays offer advertising creation services, run by an entire team of PR managers. Many commercials are creat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Many commercial advertisements are created to depict a form of art, without taking any care about ethical principles (Dojčinović & Ljajić, 2020). Some advertising involves a set of activities abusing the children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many commercial advertisements are created to depict a form of art, without taking any care about ethical principles (Dojčinović & Ljajić, 2020). Some advertising involves a set of activities abusing the children.…”
Section: Introductionmentioning
confidence: 99%
“…Some advertising involves a set of activities abusing the children. Based on analyzed commercial advertisements, Dojčinović & Ljajić (2020) concluded that children are used in advertisements as a mean of achieving economic goals, and that the children are manipulated in the advertisements.…”
Section: Introductionmentioning
confidence: 99%
“…Many commercial advertisements are created to depict a form of art, without taking any care about ethical principles (Dojčinović & Ljajić, 2020). Some advertising involves a set of activities abusing the children.…”
Section: Introductionmentioning
confidence: 99%
“…Some advertising involves a set of activities abusing the children. Based on analyzed commercial advertisements, Dojčinović & Ljajić (2020) concluded that children are used in advertisements as a mean of achieving economic goals, and that the children are manipulated in the advertisements.…”
Section: Introductionmentioning
confidence: 99%